2008
DOI: 10.1021/ef800335w
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Combustion Characteristics and Emissions of an Indirect Injection Diesel Engine under Different Operating Conditions

Abstract: In this study, the effects of engine-operating conditions on the combustion characteristics and emissions of an indirect injection (IDI) diesel engine have been experimentally investigated. The engine tests were conducted on 20, 30, and 40 N m constant loads and at full load condition. The experimental results show that the maximum cylinder gas pressures (P max) increased with an increasing engine speed and load. The location of the maximum cylinder gas pressure closed to top dead center (TDC) at high engine l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Also, the presence of ethanol in the blend increases ignition delay; hence, more fuel is accumulated in the delay period which results in rapid combustion in the premixed combustion phase causing a higher heat release rate. The heat-release profile has a slight negative dip during the ignition delay period, which is mainly heat loss from the cylinder during the fuel vaporizing phase as reported by Turkcan et al Heat released during the premixed combustion is higher for diesel−biodiesel−ethanol blends than neat diesel due to the longer ignition delay resulting from the lower cetane number and higher latent heat of vaporization of ethanol in the blend …”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…Also, the presence of ethanol in the blend increases ignition delay; hence, more fuel is accumulated in the delay period which results in rapid combustion in the premixed combustion phase causing a higher heat release rate. The heat-release profile has a slight negative dip during the ignition delay period, which is mainly heat loss from the cylinder during the fuel vaporizing phase as reported by Turkcan et al Heat released during the premixed combustion is higher for diesel−biodiesel−ethanol blends than neat diesel due to the longer ignition delay resulting from the lower cetane number and higher latent heat of vaporization of ethanol in the blend …”
Section: Resultssupporting
confidence: 52%
“…Parameters of combustion characteristics such as ignition delay, start of combustion, and the combustion duration are obtained from the heat-release curve. The start of combustion is defined as the point where the heat-release rate turns from negative to zero, and the time between the start of injection and the start of detectable heat release is denoted as the ignition delay.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar trends for the heat-release curves were observed at all other engine speeds. It was observed that the area under the heat-release rate curves increased with the increasing engine load (Turkcan and Canakci, 2009).…”
Section: Heat Release Rate Resultsmentioning
confidence: 99%